Health versus other sectors: Multisectoral resource allocation preferences in Mukono district, Uganda - Yemeke, Tatenda T; Kiracho, Elizabeth E; Mutebi, Aloysius; Apolot, Rebecca R; .Ssebagereka, Anthony; Evans, Daniel R.; Ozawa, Sachiko (Public Library of Science, 2020)
Objectives To elicit citizen preferences for national budget resource allocation in Uganda, examine respondents’ preferences for health vis-à-vis other sectors, and compare these preferences with actual government budget allocations. Methods We surveyed 432 households in urban and rural areas of Mukono district in central Uganda.We elicited citizens’ preferences for resource allocation across all sectors using a best-worst scaling (BWS) survey. The BWS survey consisted of 16 sectors corresponding to the Uganda national budget line items. Respondents chose, from a subset of four sectors across 16 choice tasks, which sectors they thought were most and least important to allocate resources to. We utilized the relative best-minus-worst score method and a conditional logistic regression to obtain ranked preferences for resource allocation across sectors. We then compared the respondents’ preferences with actual government budget allocations. Results The health sector was the top ranked sector where 82% of respondents selected health as the most important sector for the government to fund, but it was ranked sixth in national budget allocation, encompassing 6.4% of the total budget. Beyond health, water and environment, agriculture, and social development sectors were largely underfunded compared to respondents’ preferences. Works and transport, education, security, and justice, law and order received a larger share of the national budget compared to respondents’ preferences. Conclusions Among respondents from Mukono district in Uganda, we found that citizens’ preferences for resource allocation across sectors, including for the health sector, were fundamentally misaligned with current government budget allocations. Evidence of respondents’ strong preferences for allocating resources to the health sector could help stakeholders make the case for increased health sector allocations. Greater investment in health is not only essential to satisfy citizens’ needs and preferences, but also to meet the government’s health goals to improve health, strengthen health systems, and achieve universal health coverage.
Keywords: resource allocation, government, budget allocations, health sector